2007
DOI: 10.1007/s10853-006-0900-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of face-centered cubic metals processed by equal-channel angular pressing

Abstract: This review surveys the characteristics of face-centered cubic (fcc) metals and alloys processed by equal-channel angular pressing (ECAP). The significance of the Hall-Petch relationship for ultrafine grained structures is examined and the dependence of the saturated stress obtained in ECAP on the absolute melting temperature is described and discussed. In addition, the flow processes at low temperatures in ultrafine-grained materials and the microstructural evolution of the dislocation densities and precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 91 publications
(108 reference statements)
1
41
0
Order By: Relevance
“…For example, in Cu when the grain size is reduced to the range ~20-100 nm the Hall-Petch slope, k H , decreases [31]. This breakdown of Hall-Petch behavior is usually explained by the grain size dependence of the stress required to operate a Frank-Read source [34] and the strong reduction in the numbers of dislocations in pile-ups with decreasing grain size [35].…”
Section: Dislocation Density and The Hall-petch Relationshipmentioning
confidence: 99%
“…For example, in Cu when the grain size is reduced to the range ~20-100 nm the Hall-Petch slope, k H , decreases [31]. This breakdown of Hall-Petch behavior is usually explained by the grain size dependence of the stress required to operate a Frank-Read source [34] and the strong reduction in the numbers of dislocations in pile-ups with decreasing grain size [35].…”
Section: Dislocation Density and The Hall-petch Relationshipmentioning
confidence: 99%
“…They found that crystals with larger dislocation density were harder [22]. It has been shown for different pure face-centered cubic (fcc) metals processed by Equal Channel Angular Pressing (ECAP) that the dislocation density increases while grain size decreases with increasing strain and ultimately these parameters reach saturation values [23]. Above a certain grain size limit (~20 nm) the strength of materials increases with decreasing grain size [24].…”
Section: Xrd-dislocation Density and Theoretical Densitymentioning
confidence: 99%
“…Similarly , dislocation density ( δ ) and microstrain ( є ) were also calculated [13,14 ] respectively using :-The average grain size of crystallite domain calculated from Scherer data comes out to be 2.4 nm . Coherently , dislocation density and microstrain comes out to be ( D = 8 A 0 ) 0.014 * 10 14 lin 2 / m 2 and 0.0299 respectively and found to be in agreement with reported literature [15,16] .…”
Section: Fig 1 Powder Xrd Graph Of Stable Alpha (α ) Phase Alumina Namentioning
confidence: 99%